Effect of adsorption on saturated sandstone within electric double layer on solid/liquid inter-phase - Surajudeen, S. (Slovnaft VURUP a.s, 2019)
The formation of the porous medium is based on solid mineral grains, including quartzâs, carbonate, and oxides. Many studies have been conducted only for silica; the adsorption behavior of crude oil on sandstone has not been explored. This research work considered the different conce ntrations of NaCl electrolytes in molecular dynamics simulation to determine interaction of ionic adsorption on sandstone. Obtained results show that the adsorption capability of NaCl electrolyte at higher concentration indicates the interaction between components of oil and sandstone surface in which the penetration of water film and adsorption with ionic molecules improves the adsorption capability. The adsorption values in obtained result are -23.91, -27.69, -29.32, -32.89/-34.65 and -45.89 kcal/mole for concentration of 3000 ppm, 5000 ppm,7000 ppm 9000 ppm, 11000 ppm and 11000 ppm with copper-oxide respectively. Obtained results also reveal the adsorption process of oil components formation in the reservoir gives guidance to oil detaching agent in reservoir exploration. It also shows, the adsorption components alter the wettability from oil-wet to water-wet that provides a repaid distribution of fluids flow and sweep efficiency. Â© 2019